1979
DOI: 10.1001/archderm.115.8.969
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiosarcoma arising from lymphangioma circumscriptum

Abstract: A lymphangiosarcoma arose at the site of a preexisting lymphangioma circumscriptum on the skin of the anterior part of the abdominal wall. To our knowledge, this is only the second such case to be reported, and in both patients, the preexisting lymphangioma circumscriptum had been exposed to substantial x-ray therapy. Since it is possible that x-irradiation may play a role in the development of this unusual malignant neoplasm, it seems advisable that lymphangioma circumscriptum not be exposed to substantial am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…A minute number of lymphangiosarcomas were noted on sites of CLC with prior radiation therapy. 26 A Dabska tumor, or papillary intralymphatic angioendothelioma, was reported forming within an adolescent patient's CLC. The lymphangioma recurred after excision, but the Dabska tumor did not.…”
Section: Clinical Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minute number of lymphangiosarcomas were noted on sites of CLC with prior radiation therapy. 26 A Dabska tumor, or papillary intralymphatic angioendothelioma, was reported forming within an adolescent patient's CLC. The lymphangioma recurred after excision, but the Dabska tumor did not.…”
Section: Clinical Descriptionsmentioning
confidence: 99%
“…Radiation therapy should be avoided, as malignant conversion is possible. 26 Sclerotherapy with hypertonic saline may be successfully employed. 40 A large review of pediatric lymphatic malformations treated with the sclerosing agent OK-432 demonstrated success in single or limited cyst malformations (<5 in number).…”
Section: Managementmentioning
confidence: 99%
“…Lymphangiosarcoma is a rare occurrence in LC; it has been reported at the site of an irradiated LC. Squamous cell carcinoma developing in a long-standing lesion has also been reported (7,8).…”
Section: Discussionmentioning
confidence: 96%
“…19,20 Ayrıca LS lezyonu üzerinde lenfanjiyosarkom gelişen bir olgu da bulunmaktadır. 21 LS'de standart bir tedavi seçeneği yoktur. Konservatif tedavi şekilleri ön plandadır.…”
Section: Discussionunclassified